BODIPY-mediated photosensitization approach to control maize (Zea mays) pathogenic fungus Fusarium verticillioides - Aydinoglu, Fatma; Gultekin, Yagmur; Gul, Elif Yildiz; Ecik, Esra Tanriverdi (Springer, 2025)
Widespread use of fungicides has caused the fungi to gain resistance. Therefore, photodynamic inactivation (PDI) is a promising alternative to conventional fungicides. PDI uses light and a dye called a photosensitizer (PS) in the presence of oxygen to generate reactive oxygen species (ROS) in the illuminated area that eventually kills microorganisms. This study aimed to investigate the potential of novel BODIPY and commercial Rose Bengal (RB) dyes as PSs in PDI treatment on maize (Zea mays)-pathogenic fungus Fusarium verticillioides. PDI efficacy of both PSs was determined by the minimum inhibitory concentration (MIC) assay, a fluorometric assay using 2 ',7 '-dichlorofluorescein diacetate (DCFH2-DA) staining, pathogenicity test on the leaves of the host plant, and the expression of the candidate PS-targeted genes by RT-qPCR. Finally, MIC has recorded that the concentration causing the highest fungal growth inhibition was 33.38 mu g/ml for BODIPY and 134.4 mu g/ml for RB. While ROS increased by 2-fold in conidia treated to PDI with BODIPY, it was decreased by 2-fold with RB. The pathogenicity of F. verticillioides in PDI treatment with BODIPY (4 mu g/ml) or RB (16 mu g/ml) reduced by 88% or 91%. The expression of the candidate targets, Sterol 14 a-demethylase (Cyp51), mitochondrial cytochrome b (Cytb), and succinate dehydrogenase (SDH) genes were downregulated in response to PDI treatments. The results suggested that photoinactivation of fungal growth and pathogenicity increased with PS concentration, accompanied by ROS accumulation and Cyp51, Cytb, and SDH downregulation. These findings pointed out the potential of both PSs for PDI treatment as a new fungicide.
Keywords: Zea mays; Fusarium verticillioides; Photodynamic inactivation; Minimum inhibitory concentration